The Appropriateness Of A Risk Stratification Procedure For Thromboembolism Prophylaxis After Total Knee Replacement Surgeries - Ahmad Abdeljalil Alameri, Mariam (2020)
Total knee replacement (TKR) is one of the major orthopedic surgeries, which is considered one solution for patients with degenerative joint disease. These surgeries are considered high risk surgeries for the development of venous thromboembolism (VTE). Limiting both VTE events and bleeding episodes is essential; since the bleeding has a negative impact on the surgical outcomes, so, excessive anticoagulation should be avoided. The primary objective in this study is to evaluate the clinical outcomes for the use of a VTE risk stratification procedure for selecting the extended VTE prophylaxis post-TKR Surgeries.